Hot stamped compact
Patent Information
- Application Number
- JP2024532838
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2023-03-10
- Filing Date
- 2024-03-08
- Publication Date
- 2025-02-27
- Estimated Expiration
- 2044-03-08
AI Technical Summary
【0017】 本発明によれば、ホットスタンプ工程で部分的に高い歪が導入される場合においても、高歪領域におけるホットスタンプ成形後の強度の低下が抑制され、かつ優れた耐水素脆化特性および高い切欠き引張強さを備えたホットスタンプ成形体を得ることができる。
Smart Images

Figure 0007636704000008 
Figure 0007636704000009 
Figure 0007636704000010
Abstract
Description
[Technical field]
[0001] The present invention relates to a hot stamped product. [Background technology]
[0002] In order to achieve both weight reduction and collision safety in automobiles, there is a demand for higher strength materials used in automobiles. For this reason, hot stamped steel up to 1.8 GPa has been put to practical use in recent years for automobile bodies. In addition, if chassis parts are also required to have the same high strength as the automobile body, it will be necessary to consider using hot stamped steel in the future.
[0003] In the above-mentioned automobile parts, burring may be performed in order to assemble the parts together, etc. For example, Patent Document 1 discloses a method for manufacturing a hot-pressed product having a burred portion.
[0004] The manufacturing method disclosed in Patent Document 1 includes a heating step of heating a plate material and a forming step of forming the heated plate material. In the forming step, in addition to forming the plate material, quenching and burring are performed. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] JP 2019-58916 A Summary of the Invention [Problem to be solved by the invention]
[0006] However, as a result of the study by the present inventors, it was found that in the region where high strain is applied, such as the burring portion, during hot stamp forming, ferrite may be generated and the material may be partially softened. This is believed to be because the high strain promotes diffusion transformation. Furthermore, the results of various studies using a hot working simulator revealed that the greater the processing strain, the lower the hardenability, and that it is necessary to increase the critical cooling rate for obtaining a sound full martensite structure in the subsequent cooling process.
[0007] Since chassis parts use relatively thick steel, the cooling rate by die cooling is slower than that of the thin steel used for the body. From this perspective, it is thought that the decrease in hardenability is likely to become apparent in areas where high processing strain is introduced. Even in body parts where hot stamping steel sheets are already used, the structure is complicated in order to control the deformation form of each part, and high strain may be introduced in some parts.
[0008] Furthermore, from the viewpoint of further improving safety, automobile parts and the like are also required to have both excellent hydrogen embrittlement resistance and high notch tensile strength.
[0009] An object of the present invention is to solve the above problems and to provide a hot stamped steel in which the decrease in strength after hot stamping in a high strain region is suppressed even when a large strain is locally introduced in the hot stamping process, and which has excellent hydrogen embrittlement resistance and high notch tensile strength. [Means for solving the problem]
[0010] The present invention has been made in order to solve the above-mentioned problems, and the gist of the present invention is the following hot stamped product.
[0011] (1) a first region having a metal structure in which an area ratio of martensite is 95% or more and an average aspect ratio of prior austenite grains is 1.10 or less; A second region having a metal structure in which the area ratio of martensite is 95% or more and the average aspect ratio of prior austenite grains is 2.00 or more, When the average grain size of the prior austenite grains in the first region is G1 (μm) and the average grain size of the prior austenite grains in the second region is G2 (μm), G1 is 15.0 μm or less and G2 is 25.0 μm or less, and the following formula (i) is satisfied: The tensile strength measured by a tensile test using a test piece taken from the first region is 1250 to 2540 MPa. Hot stamped compact. G2-G1≧3.0 (i)
[0012] (2) the average grain size G1 of the prior austenite grains in the first region is 5.0 to 15.0 μm, and the average grain size G2 of the prior austenite grains in the second region is 10.0 to 25.0 μm; The hot stamped product according to (1) above.
[0013] (3) Chemical composition, in mass%, C: 0.10-0.60%, Si: 0.01 to 2.00%, Mn: 0.10-3.00%, P: 0.050% or less, S: 0.0200% or less, N: 0.0200% or less, O: 0.100% or less, Al: 0.001 to 0.100%, Cr: 0.01 to 1.00%, Nb: 0 to 0.200%, Ti: 0 to 0.200%, Mo: 0-1.00%, B: 0~0.0100%, Co: 0-4.00%, Ni: 0-2.00%, Cu: 0-1.00%, V: 0~1.00%, W: 0 to 1.00%, Ca: 0 to 0.0100%, Mg: 0 to 0.0100%, REM: 0~0.0100%, Sb: 0 to 0.100%, Zr: 0 to 0.100%, Sn: 0-1.00%, As: 0~0.100%, The balance is Fe and impurities. The hot stamped compact according to (1) or (2) above.
[0014] (4) a first region having a metal structure in which an area ratio of martensite is 95% or more and an average aspect ratio of prior austenite grains is 1.10 or less; A second region having a metal structure in which the area ratio of martensite is 95% or more and the average aspect ratio of prior austenite grains is 2.00 or more, When the average grain size of the prior austenite grains in the first region is G1 (μm) and the average grain size of the prior austenite grains in the second region is G2 (μm), G1 is 15.0 μm or less and G2 is 25.0 μm or less, and the following formula (i) is satisfied: The tensile strength measured by a tensile test using a test piece taken from the first region is 1250 to 2040 MPa. Hot stamped compact. G2-G1≧3.0 (i)
[0015] (5) The average grain size G1 of the prior austenite grains in the first region is 5.0 to 15.0 μm, and the average grain size G2 of the prior austenite grains in the second region is 10.0 to 25.0 μm. The hot stamped compact according to (4) above.
[0016] (6) Chemical composition, in mass%, C: 0.10-0.40%, Si: 0.01 to 2.00%, Mn: 0.10-3.00%, P: 0.050% or less, S: 0.0200% or less, N: 0.0200% or less, O: 0.100% or less, Al: 0.010 to 0.100%, Cr: 0.01 to 1.00%, Nb: 0 to 0.200%, Ti: 0 to 0.200%, Mo: 0-1.00%, B: 0~0.0100%, Co: 0-4.00%, Ni: 0-2.00%, Cu: 0-1.00%, V: 0~1.00%, W: 0 to 1.00%, Ca: 0 to 0.0100%, Mg: 0 to 0.0100%, REM: 0~0.0100%, Sb: 0 to 0.100%, Zr: 0 to 0.100%, Sn: 0-1.00%, As: 0~0.100%, The balance is Fe and impurities. The hot stamped compact according to (4) or (5) above. Effect of the Invention
[0017] According to the present invention, even when high strain is introduced locally in the hot stamping process, a decrease in strength in the high strain region after hot stamping is suppressed, and a hot stamped body having excellent hydrogen embrittlement resistance and high notch tensile strength can be obtained. [Brief description of the drawings]
[0018] [Figure 1] FIG. 1 is a schematic diagram showing a molded body having a circular burring portion. [Diagram 2] FIG. 2 is a schematic diagram for explaining an example of the second measurement region. [Diagram 3] FIG. 3 is a schematic diagram showing a molded body having an elliptical burred portion. [Figure 4] FIG. 4 is a schematic diagram showing a molded product having an arc-shaped flange portion. [Diagram 5] FIG. 5 is a schematic diagram for explaining an example of the second measurement region. [Figure 6] FIG. 6 is a schematic diagram showing a molded body having a flange deformation portion. [Figure 7] FIG. 7 is a schematic diagram for explaining an example of the second measurement region. [Figure 8] FIG. 8 is a schematic diagram for explaining an example of the first measurement region. [Figure 9] FIG. 9 is a schematic diagram showing the shape of a sub-size plate test piece according to the ASTM standard. [Figure 10] FIG. 10 is a diagram for explaining the shape of a tensile test specimen used for evaluating hydrogen embrittlement resistance and notched tensile strength. [Figure 11] FIG. 11 is a diagram for explaining the procedure for cutting out a test piece from the burring portion and preparing a tensile test piece. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0019] The present inventors have investigated methods for suppressing the deterioration of hardenability in a high strain region and have come to the following findings.
[0020] An example of a high strain region is a burring portion. In the burring portion, the die may be designed to lightly squeeze the steel sheet (in the following description, the steel sheet before hot stamp forming is also referred to as a "blank"), so there is a high possibility that a direct water-cooled die cannot be applied. Furthermore, there is a possibility that the die and the blank cannot be sufficiently adhered to each other over the entire burring portion. Due to the promotion of diffusion transformation by the introduction of high strain and the difficulty of ensuring the cooling rate, it is considered that softening due to the generation of ferrite is likely to occur.
[0021] As a result of repeated experiments under various hot stamping conditions, it was found that increasing the heating temperature before hot stamping and coarsening the metal structure before processing are effective in ensuring hardenability.
[0022] However, if the heating temperature of the entire blank is increased, the metal structure will become coarse even in the low strain region, and the specific surface area of the grain boundaries will become smaller, which may result in a decrease in hydrogen embrittlement resistance and notch tensile strength.
[0023] Therefore, by heating the areas of the steel sheet before hot stamping, where high strain is expected to be added, at higher temperatures than the other areas, it is possible to improve the hardenability in the high strain areas and suppress a decrease in strength of the hot stamped body as a whole.
[0024] In addition, in the high strain region, the aspect ratio of the crystal grains increases due to the effects of processing. For the same crystal grain size, the larger the aspect ratio, the larger the specific surface area of the grain boundary. Therefore, even if the grains are coarsened in the high strain region, the degree of deterioration in hydrogen embrittlement resistance and notch tensile strength is relatively low.
[0025] The present invention has been made based on the above findings. Each feature of the present invention will be described in detail below.
[0026] 1. Metal structure of hot stamped body The hot stamped body according to this embodiment has a first region having a metal structure in which the area ratio of martensite is 95% or more and the average aspect ratio of the prior austenite grains is 1.10 or less, and a second region having a metal structure in which the area ratio of martensite is 95% or more and the average aspect ratio of the prior austenite grains is 2.00 or more.
[0027] The first region is a region where high strain was not introduced during hot stamp forming. Therefore, the average aspect ratio of the prior austenite grains in the first region is 1.10 or less. The practical lower limit of the average aspect ratio is 1.00. In addition, the metal structure is mainly composed of martensite due to the quenching associated with the hot stamp forming, and specifically, the area ratio of martensite is 95% or more. In the present invention, martensite includes not only fresh martensite as quenched, but also tempered martensite and self-tempered martensite.
[0028] In the metal structure of this embodiment, the remainder other than martensite is bainite, retained austenite, ferrite, and pearlite. However, in the present invention, as described below, the area ratio of martensite is measured based on Vickers hardness, so martensite whose hardness has been excessively reduced by tempering or self-tempering is excluded from martensite and included in the remainder.
[0029] On the other hand, the second region is a region where high strain is introduced during hot stamp forming, and as a result, the average aspect ratio of the prior austenite grains is 2.00 or more. As described above, in the region where high strain is introduced, diffusion transformation is promoted, so that ferrite is generated and not only the material becomes soft, but also hydrogen embrittlement resistance and notch tensile strength may decrease. However, in the second region, the area ratio of martensite is 95% or more because the hardenability is improved by increasing the heating temperature before hot stamp forming.
[0030] In addition, in forming that does not cause fracture, it is generally difficult to make the average aspect ratio of the prior austenite grains exceed 3.00. Therefore, the average aspect ratio of the prior austenite grains in the second region is substantially 3.00 or less. In other words, a region in which the average aspect ratio of the prior austenite grains exceeds 3.00 is considered to be a region that has not been formed appropriately, and is therefore excluded from the second region.
[0031] In the hot stamped steel according to this embodiment, even when a large strain is applied, the second region has a martensite area ratio of 95% or more, which not only suppresses a decrease in strength but also makes it possible to improve hydrogen embrittlement resistance and notch tensile strength.
[0032] As described above, in the second region, the heating temperature before hot stamp forming is increased to improve hardenability. On the other hand, the heating temperature in the first region is lower than that in the second region so as not to cause the crystal grains to become coarse. Due to this difference, the crystal grain size in the second region is larger than that in the first region. Specifically, when the average crystal grain size of the prior austenite grains in the first region is G1 (μm) and the average crystal grain size of the prior austenite grains in the second region is G2 (μm), the following formula (i) is satisfied. G2-G1≧3.0 (i)
[0033] G1 is smaller than G2 by 3.0 μm or more, that is, the metal structure in the first region is a relatively fine-grained structure, and therefore excellent hydrogen embrittlement resistance and high notch tensile strength are obtained.
[0034] The value of G2-G1 is preferably 4.0 μm or more, and more preferably 5.0 μm or more. On the other hand, although there is no need to set an upper limit to the value of G2-G1, it is industrially difficult to change the heating temperature drastically in both ranges, so that G2-G1 is 17.0 μm or less.
[0035] In addition, if the crystal grains in the first and second regions are excessively coarse, the hydrogen embrittlement resistance and notch tensile strength in each region may decrease. Therefore, G1 is set to 15.0 μm or less, and G2 is set to 25.0 μm or less. The difference in the upper limit of the average crystal grain size between the two regions is due to the difference in the aspect ratio of the crystal grains, as described above.
[0036] Although there is no particular restriction on the lower limit of G1 and G2, from the viewpoint of providing excellent hydrogen embrittlement resistance and high notch tensile strength in a 1.3 to 2.5 GPa class hot stamped steel, for example, G1 is preferably in the range of 5.0 to 15.0 μm and G2 is preferably in the range of 10.0 to 25.0 μm. G1 is more preferably 8.0 μm or more and G2 is more preferably 15.0 μm or more.
[0037] In addition, there is a so-called trade-off relationship between hydrogen embrittlement resistance and notch tensile strength, and the higher the strength of the hot stamped steel, the higher the notch tensile strength is, but the hydrogen embrittlement resistance tends to decrease. From the viewpoint of emphasizing the balance between hydrogen embrittlement resistance and notch tensile strength, the strength of the hot stamped steel is preferably 1.5 GPa class. In addition, in the case of a 1.5 GPa class hot stamped steel, from the viewpoint of providing excellent hydrogen embrittlement resistance and high notch tensile strength, it is preferable that G1 is in the range of 8.0 to 14.0 μm and G2 is in the range of 17.0 to 25.0 μm.
[0038] In the present invention, the metal structure of the hot stamped body is measured by the following method. First, the measurement region is determined. In this case, a portion of the hot stamped body that has been processed to a low degree and has not been subjected to high strain is selected as the measurement region of the first region (hereinafter also referred to as the "first measurement region"), while a portion where high strain has been introduced, such as a burred portion, can be selected as the measurement region of the second region (hereinafter also referred to as the "second measurement region").
[0039] Next, the martensite area ratio and the average crystal grain size and average aspect ratio of the prior austenite grains are measured for the above measurement regions (first measurement region and second measurement region, respectively). In the present invention, the martensite area ratio is measured by combining observation with a field emission scanning electron microscope (FE-SEM) and Vickers hardness measurement, and the average crystal grain size and average aspect ratio of the prior austenite grains are measured by analysis using electron backscatter diffraction (EBSD). Each measurement procedure will be described in more detail.
[0040] After the measurement area is etched with nital, a secondary electron image of a 300 μm long and 2000 μm wide area centered on a 1 / 4 depth position (hereinafter referred to as the "1 / 4 thickness position") from the surface of the base steel plate in the measurement area is taken at 1000 times magnification using an FE-SEM. That is, an FE-SEM equipped with a secondary electron detector is used. Then, image analysis is performed on the obtained structural photograph to measure the area ratio of structures determined to be ferrite or pearlite, and the rest are determined to be martensite, bainite, or retained austenite. If the total area ratio determined to be martensite, bainite, or retained austenite is 95% or more, a mesh is drawn at 70 μm intervals in the 300 μm long and 2000 μm wide area, and Vickers hardness is measured at all intersections of the mesh (4 × 28 = 112 points). The test force for the Vickers hardness measurement is 0.98 N (0.1 kgf). Then, the specimen is photographed again at 1000x magnification using an FE-SEM. By comparing the microstructure photographs taken before and after the Vickers hardness measurement, it is possible to determine whether the indentation made by pressing the indenter in the Vickers hardness measurement (hereinafter simply referred to as the "indentation") contains a structure other than martensite, bainite, and retained austenite, i.e., ferrite or pearlite.
[0041] Then, among the obtained Vickers hardness measurements, the average of the measurements that are identified as containing only martensite, bainite or retained austenite within the range of the depressions remaining on the surface is calculated, and if the following formula is satisfied, it is determined that the area ratio of martensite in the metal structure is 95% or more. Note that "HV0.1" below refers to the "hardness symbol" when a Vickers hardness test is conducted with a test force of 0.98N (0.1kgf) (see JIS Z 2244-1:2020). HV MBγ ≧957.1×[C]+221.0 In the above formula, the meanings of each symbol are as follows: HV MBγ : Average Vickers hardness measurement value (HV0.1) that identifies an indentation as containing only martensite, bainite or retained austenite [C]: C content of hot stamped compact (mass%)
[0042] If it is not possible to secure an area of 300 μm in length and 2000 μm in width within the measurement area, for example, four areas of 300 μm in length and 500 μm in width may be secured, and the above-mentioned FE-SEM observation and Vickers hardness measurement may be performed in each area.
[0043] Next, the above measurement area is polished using #600 to #1500 silicon carbide paper, and then finished to a mirror surface using a liquid in which diamond powder with a grain size of 1 to 6 μm is dispersed in a diluted solution such as alcohol or pure water. Next, the sample is polished for 8 minutes at room temperature using colloidal silica with a grain size of 0.25 μm that does not contain an alkaline solution to remove the strain introduced into the surface layer of the sample.
[0044] Then, EBSD measurements are performed at 0.1 μm intervals on an area of 300 μm length and 500 μm width centered at the 1 / 4 thickness position of the measurement area to obtain crystal orientation information. For the measurements, an EBSD analysis device consisting of an FE-SEM and an EBSD detector can be used, for example, an EBSD analysis device consisting of a JEOL JSM-7001F and an AMETEK Hikari detector. In this case, for example, the degree of vacuum inside the EBSD analysis device is 9.6×10 -5 Pa or less, acceleration voltage is 20 kV, working distance (WD) is 15 mm, probe current level is 18, and the inclination angle of the specimen is 70°.
[0045] The EBSD pattern is collected using the "AMETEK OIM Data Collection" software that comes with the EBSD analysis device. The analysis is performed by selecting the crystal structure as Iron (Alpha) and Iron (Gamma). Using the obtained crystal orientation information, the crystal orientation of the prior austenite grains is calculated from the crystal orientation relationship between general prior austenite grains and crystal grains with a bcc structure after transformation.
[0046] The crystal orientation of the prior austenite grains may be calculated by the following method: First, the prior austenite grains are identified by the method described in "Study on High-Precision Reconstruction Method of Austenite Structure of Steel" (Hata Kengo, Wakita Masayuki, Fujiwara Tomoya, Kono Kaori, Nippon Steel & Sumitomo Metal Technical Report No. 404 (2016), pp. 24-30).
[0047] In addition, when adopting the method described in the above document, in the present invention, the orientation relationship between ferrite and austenite is set to a KS relationship. In the present invention, in addition to ferrite, the structures determined to have a bcc structure by EBSD include pearlite, fresh martensite, tempered martensite, and bainite, and the structures determined to have an fcc structure include retained austenite. Therefore, the structures determined to have a bcc structure by EBSD are regarded as ferrite, and the structures determined to have an fcc structure are regarded as austenite. In addition, the allowable angle described in the above document is set to 3 degrees, and the allowable error is set to 5 degrees.
[0048] The data of the austenite grains that could not be reconstructed by the above procedure is saved as ferrite grains (bcc structure). In other words, they are not converted to austenite (fcc structure). For each identified prior austenite grain, excluding prior austenite grains that are not entirely included in the field of view, such as the edge of the field of view, the grain size is obtained from the Area Fraction of the "Grain Size (diameter)" chart in "AMETEK OIM Analysis (registered trademark)", and the aspect ratio is obtained by obtaining the inverse of the "Grain Shape Aspect Ratio". Here, the inverse of the "Grain Shape Aspect Ratio" is used because the "Grain Shape Aspect Ratio" is the minor axis / major axis. In this case, the boundary where the orientation difference is 15 degrees or more is regarded as the grain boundary of austenite.
[0049] In the present invention, the crystal grain size means the circle-equivalent diameter, and the aspect ratio means the ratio of the length in the major axis direction to the length in the direction perpendicular thereto.
[0050] The shape of the hot stamped product according to this embodiment is not particularly limited, but has a portion including a first region where large strain is not introduced and a portion including a second region where large strain is introduced. The thickness of the portion where large strain is not introduced is preferably 1.0 to 4.0 mm, and the thickness of the portion where large strain is introduced is preferably 0.6 to 3.0 mm, and more preferably 1.0 to 3.0 mm.
[0051] Furthermore, a suitable measurement region will be described using a typical hot stamped product as an example. Examples of the hot stamped product according to this embodiment include a product having a circular burred portion as shown in Fig. 1, a product having an elliptical burred portion as shown in Fig. 3, a product having an arc-shaped flange portion as shown in Fig. 4, and a product having a flange deformation portion as shown in Fig. 6. The suitable measurement region for each product will be described in detail below.
[0052] FIG. 1 is a schematic diagram showing a molded body having a circular burring part, where (a) is a perspective view, (b) is a plan view, and (c) is a side view. As shown in FIG. 1, the molded body 100 has a plate-shaped part 10 and a cylindrical burring part 12 rising from the plate-shaped part 10. The thickness t1 of the plate-shaped part 10 is, for example, 1.0 to 4.0 mm, and the thickness t2 at the tip of the burring part 12 is, for example, 0.6 to 3.0 mm. The height L of the burring part 12 (the distance between the plate-shaped part 10 and the tip of the burring part 12 in the thickness direction of the plate-shaped part 10) is, for example, 3 to 30 mm. In addition, when viewed from the thickness direction of the plate-shaped part 10, the diameter (inner diameter) φ of the tip of the burring part 12 is, for example, 15 to 100 mm.
[0053] In the present invention, the molded body may be plated. In the present specification, the "thickness" refers to the thickness of the base material obtained by subtracting the plating thickness from the total thickness. The plating thickness is measured by a high-frequency glow discharge optical emission surface analyzer (GDS). A specific measurement method is described below.
[0054] Three arbitrary measurement positions are determined in each of the first and second regions of the hot stamped body, which have a coating layer. The element concentrations of Fe, Mn, Zn, Si, Al, O, Cr, Ni, Mg, Cu, and Sn are measured at each measurement position while sputtering is performed from the surface of the coating layer.
[0055] The content of each element is analyzed in the depth direction, and the depth at which the Fe concentration first reaches 90% or more is determined. The average depth at each measurement point is then calculated, and this average is taken as the plating thickness for each of the first and second regions. If the Fe concentration does not reach 90% or more at the depth that can be analyzed in one GDS measurement, that is, if the plating layer is thicker than the measured depth, the plating layer equivalent to 80-90% of the previously measured depth is removed by polishing at an arbitrary position other than the previously measured position in the same region, and the depth of the plating layer removed by polishing is determined from the change in plate thickness before and after polishing. A new GDS analysis is then performed from the polished surface, and the plating thickness is measured by combining the results of the first and second measurements.
[0056] As a measuring device for GDS, for example, a Marcus type high frequency glow discharge optical emission spectrometer GD-Profiler2 (manufactured by HORIBA) is used. In this case, for example, the discharge conditions are 35 W, the Ar pressure during measurement is 600 Pa, the discharge range is 4 mm in diameter, the electrode distance is 0.15 to 0.25 mm, and the measurement pitch in the plate thickness direction is 0.01 to 0.05 μm.
[0057] 1, the burring portion 12 is formed to rise perpendicularly to the plate-shaped portion 10, but the burring portion 12 may rise at an angle to the plate-shaped portion 10. For example, the burring portion 12 may be formed to have a smaller diameter toward the tip end side (the further away from the plate-shaped portion 10 in the thickness direction of the plate-shaped portion 10).
[0058] In the molded body 100, a large strain is introduced in the burring portion 12, and the strain becomes higher toward the tip and toward the outer edge. Therefore, a cross section at a position distanced d from the tip of the burring portion 12 toward the plate-like portion 10 can be cut out, and a second measurement region can be selected from the cross section. The distance d is, for example, 0.5 to 1.0 mm.
[0059] 2 is a schematic diagram for explaining an example of the second measurement region, where (a) is a cross-sectional view of the aa portion of FIG. 1(c), and (b) is an enlarged view of the region indicated by the dotted line in (a). In FIG. 2(b), hatching is not applied to avoid the drawing becoming complicated. As shown in FIG. 2(b), the region of 300 μm in length and 2000 μm in width indicated by the dashed line centered at the position of t2 / 4 from the outer edge of the burring portion 12 can be used as the FE-SEM observation region, and the region of 300 μm in length and 500 μm in width indicated by the dashed line can be used as the EBSD analysis region.
[0060] Fig. 3 is a schematic diagram showing a molded body having an elliptical burred portion, where (a) is a plan view and (b) is a cross-sectional view. In the molded body 100 shown in Fig. 1, the burred portion 12 is circular when viewed from the thickness direction of the plate-like portion 10, but as in the molded body 200 shown in Fig. 3, the burred portion 22 may be elliptical when viewed from the thickness direction of the plate-like portion 20. When viewed from the thickness direction of the plate-like portion 20, the short diameter (inner diameter) φ1 of the tip of the burred portion 22 is, for example, 10 to 80 mm, and the long diameter (inner diameter) φ2 is, for example, 15 to 100 mm.
[0061] When the burring portion 22 has an elliptical shape, a higher strain is imparted to the region with a larger degree of curvature on the major axis side, so the second measurement region can be selected from the region indicated by the dotted line in FIG. 3(b). The positions of the FE-SEM observation region and the EBSD analysis region are the same as those described above, so their explanations are omitted. Note that FIG. 3(b) is a cross-sectional view at a position distanced d from the tip of the burring portion 22 toward the plate-shaped portion 20, and the distance d is, for example, 0.5 to 1.0 mm.
[0062] FIG. 4 is a schematic diagram showing a molded body having an arc-shaped flange portion, where (a) is a perspective view, (b) is a plan view, and (c) is a side view. As shown in FIG. 4, the molded body 300 has a plate-shaped portion 30 and an arc-shaped flange portion 32 rising from the plate-shaped portion 30. The thickness t1 of the plate-shaped portion 30 is, for example, 1.0 to 4.0 mm, and the thickness t2 at the tip of the flange portion 32 is, for example, 0.6 to 3.0 mm. The height L of the flange portion 32 (the distance between the plate-shaped portion 30 and the tip of the flange portion 32 in the thickness direction of the plate-shaped portion 30) is, for example, 3 to 30 mm. When viewed from the thickness direction of the plate-shaped portion 30, the flange portion 32 has an arc shape, and the radius of curvature R is, for example, 50 to 500 mm.
[0063] In the molded body 300, a large strain is introduced in the flange portion 32, and the strain increases toward the outside of the arc (the side farther from the center of curvature). Therefore, a cross section at a position distanced d from the tip of the flange portion 32 toward the plate-like portion 30 can be cut out, and a second measurement region can be selected from the cross section. The distance d is, for example, 0.5 to 1.0 mm.
[0064] 5 is a schematic diagram for explaining an example of the second measurement region, where (a) is a cross-sectional view of the bb portion of FIG. 4(c), and (b) is an enlarged view of the region indicated by the dotted line in (a). In FIG. 5(b), hatching is not applied to avoid the drawing becoming complicated. As shown in FIG. 5(b), the region of 2000 μm in length and 300 μm in width indicated by the dashed line centered at the position of t2 / 4 from the outside of the arc of the flange portion 32 can be used as the observation region of the FE-SEM, and the region of 500 μm in length and 300 μm in width indicated by the dashed line can be used as the analysis region of the EBSD.
[0065] FIG. 6 is a schematic diagram showing a molded body having a flange deformation portion, where (a) is a perspective view, (b) is a plan view, and (c) is a cross-sectional view of the cc portion of (b). As shown in FIG. 6, the molded body 400 has a plate-shaped portion 40, a cylindrical portion 42 rising from the plate-shaped portion 40, and an annular inner flange portion 44 protruding inward from the cylindrical portion 42 and having a hole in the center. The thickness t1 of the plate-shaped portion 40 is, for example, 1.0 to 4.0 mm, and the thickness t2 of the cylindrical portion 42 and the thickness t3 of the inner flange portion 44 are, for example, 0.6 to 3.0 mm. The height L of the cylindrical portion 42 (the distance between the plate-shaped portion 40 and the inner flange portion 44 in the thickness direction of the plate-shaped portion 40) is, for example, 3 to 30 mm. When viewed from the thickness direction of the plate-shaped portion 40, the diameter (inner diameter) φ of the hole of the inner flange portion 44 is, for example, 10 to 100 mm.
[0066] In the molded body 400, a large strain is introduced into the inner flange portion 44, and the strain becomes higher on the inner side (the side closer to the hole). Therefore, a cross section at a position t3 / 4 away from the outer surface of the inner flange portion 44 toward the plate-like portion 40 can be cut out, and a second measurement region can be selected from the cross section.
[0067] FIG. 7 is a schematic diagram for explaining an example of the second measurement region, where (a) is a cross-sectional view of the dd portion of FIG. 6(c), and (b) is an enlarged view of the region indicated by the dotted line in (a). In FIG. 6(b), hatching is not applied to avoid the drawing becoming complicated. As shown in FIG. 6(b), a region of 2000 μm in length and 300 μm in width indicated by a dashed line centered at a position distant from the hole of the inner flange portion 44 by a distance d can be used as the observation region of the FE-SEM, and a region of 500 μm in length and 300 μm in width indicated by a dashed line can be used as the analysis region of the EBSD. The distance d is, for example, 0.5 to 1.0 mm.
[0068] As described above, all the molded bodies have a plate-like portion, but the plate-like portion is a portion to which high strain has not been introduced. Therefore, it is preferable to select the first measurement region from the plate-like portion. The first measurement region will be described in more detail with reference to Figs. 1 and 8. Fig. 8 is a schematic diagram for explaining an example of the first measurement region, in which (a) is a cross-sectional view of the ee portion of Fig. 1(b), and (b) is an enlarged view of the region indicated by the dotted line in (a). In Fig. 8(b), hatching is not applied to avoid complicating the drawing. As shown in Fig. 1, a cross section parallel to the thickness direction of the plate-like portion 10 and a cross section at a distance D from the boundary where the plate-like portion 10 and the burring portion 12 are connected can be cut out, and the first measurement region can be selected from the cross section. The distance D is, for example, 7 to 8 mm. As shown in Figure 8(b), the region 300 μm long and 2000 μm wide indicated by the dashed line, centered at a position t1 / 4 from the surface of the plate-shaped portion 10, can be used as the FE-SEM observation region, and the region 300 μm long and 500 μm wide indicated by the dotted line can be used as the EBSD analysis region.
[0069] 2. Mechanical properties In the hot stamped steel according to the present embodiment, the tensile strength measured by a tensile test using a test piece taken from the first region is 1250 to 2540 MPa. By having the above strength, when the hot stamped steel is used as an automobile part, it is possible to contribute to weight reduction of the automobile and ensuring collision safety. The above tensile strength is preferably 1250 to 2040 MPa. Furthermore, as described above, when importance is attached to the balance between the hydrogen embrittlement resistance and notch tensile strength of the hot stamped steel, it is preferable that the hot stamped steel has a strength of 1.5 GPa class, and specifically, the above tensile strength is preferably 1450 to 1540 MPa.
[0070] In the present invention, the tensile strength is measured using a sub-size plate-shaped test piece (width 10 mm, total length 100 mm, parallel part width 6.25 mm, parallel part length 32 mm, gauge length 25 mm, thickness: original thickness of the first region) specified in ASTM A370-22, the shape of which is shown in FIG. 9, and the tensile speed is a crosshead displacement speed of 3 mm / min. Other conditions are to be performed in accordance with JIS Z 2241:2022. As described above, when the molded body is plated, the tensile strength is measured using a test piece in a plated state, and the "thickness: original thickness of the first region" is the thickness of the base material part obtained by subtracting the plating thickness from the total thickness. In other words, the original cross-sectional area of the test piece used to calculate the tensile strength is the original cross-sectional area of the base material part excluding the plating layer. The plating thickness is to be measured in the same manner as above.
[0071] As described above, by forming the metal structure mainly composed of martensite in the second region in addition to the first region, local softening is suppressed. Therefore, it is possible to reduce the difference in hardness between the first region and the second region. From this viewpoint, in the hot stamped steel according to the present embodiment, when the average hardness in the first region is HV1 (HV0.1) and the average hardness in the second region is HV2 (HV0.1), it is preferable that the following formula (ii) is satisfied. The right-hand side value of the following formula (ii) is more preferably 30.0, and even more preferably 20.0. |HV1-HV2|≦40.0 (ii)
[0072] The average hardness HV1 in the first region and the average hardness HV2 in the second region are determined to be the average values of the measured Vickers hardness at all intersections of the mesh with 70 μm intervals described above.
[0073] Furthermore, it is preferable that HV1 and HV2 satisfy the following formulas (iii) and (iv), respectively. 997.6×[C]+230.4≦HV1≦1133.9×[C]+281.8 (iii) 997.6×[C]+230.4≦HV2≦1133.9×[C]+281.8 (iv) In the above formula, [C] means the C content (mass%) of the hot stamped steel.
[0074] The hot stamped steel according to this embodiment has excellent hydrogen embrittlement resistance and high notch tensile strength. However, as described above, there is a so-called trade-off relationship between hydrogen embrittlement resistance and notch tensile strength. Therefore, in this embodiment, for example, when the sum of the fracture stress in a hydrogen environment, which is an index of hydrogen embrittlement resistance, and the notch tensile strength is 2400 MPa or more, it can be determined that the hot stamped steel has excellent hydrogen embrittlement resistance and high notch tensile strength.
[0075] The fracture stress and notch tensile strength in a hydrogen environment can be evaluated by the following method. First, two tensile test pieces having the shape shown in FIG. 10 are taken from each of the hot stamped bodies. It is preferable that the above tensile test pieces are taken from each of the first region and the second region, and evaluation is performed for each region. In this case, the tensile test pieces are taken so that a position at a depth of 1 / 2 the thickness from the surface of the base steel plate overlaps with at least a part of the bottom of the U-notches on both sides formed in the tensile test pieces.
[0076] It may not be possible to take the above tensile test specimens from the burring section due to dimensional constraints. In that case, as shown in an example in Figure 11, a test specimen of the possible size is taken from the burring section, and a U-notch is formed on both sides of the taken test specimen. However, the length of the taken test specimen must be 6.0 mm or more. Then, other dummy materials are welded to both sides of the test specimen so that the test specimen is placed in the center of the tensile test specimen shown in Figure 10. At this time, the test specimen is laser-welded while being clamped between copper jigs to prevent the heat effect of welding from reaching the part with the U-notches on both sides.
[0077] Also, due to dimensional constraints, it may not be possible to obtain a 1.0 mm thick tensile test piece as shown in Figure 10 or a 1.0 mm thick test piece as shown in Figure 11. In that case, two 0.5 mm thick tensile test pieces are prepared as described above, and then joined by screws or welding to obtain a 1.0 mm thick tensile test piece. The joining by screws or welding should be performed at the center position in the height direction of the grips formed on both ends of the tensile test piece (on the dashed line in the figure).
[0078] One of the tensile test pieces was placed in a 3% NaCl aqueous solution as the cathode, and a current density of 1.0 mA / cm 2 While generating hydrogen on the surface of the tensile test piece under the above conditions, a tensile test is performed at a tensile speed of 0.006 mm / min, and the breaking stress (maximum stress) is measured. The measured breaking stress is a value that serves as an index of hydrogen embrittlement resistance, and is the tensile strength in a hydrogen environment.
[0079] For the other tensile test piece, a tensile test is carried out in air at 0.006 mm / min in accordance with JIS Z 2241:2022 to measure the breaking stress (maximum stress), and the measured value obtained is regarded as the notch tensile strength.
[0080] 3.Chemical composition The chemical composition of the hot stamped steel according to this embodiment is not particularly limited as long as it has the above-mentioned strength. For example, the hot stamped steel according to this embodiment preferably has the chemical composition shown below. The reasons for limiting each element are as follows. In the following description, "%" for the content means "mass%".
[0081] C: 0.10-0.60% C is an element that improves the strength of the hot stamped body. Therefore, the C content is preferably 0.10% or more. The C content is more preferably more than 0.10%, 0.15% or more, 0.20% or more, or 0.25% or more. From the viewpoint of weldability, the C content is preferably 0.60% or less. More preferably, the C content is 0.50% or less, 0.40% or less, 0.38% or less, 0.37% or less, 0.35% or less, or 0.30% or less. The C content is preferably 0.10 to 0.50%, 0.10 to 0.40%, more than 0.10% and 0.38% or less, 0.15 to 0.37%, 0.20 to 0.35%, or 0.25 to 0.30%.
[0082] Silicon: 0.01 to 2.00% Si is an element that improves the strength of a hot stamped body by solid solution strengthening. Therefore, the Si content is preferably 0.01% or more. The Si content is more preferably 0.05% or more, 0.10% or more, 0.20% or more, 0.30% or more, or 0.40% or more. On the other hand, if the Si content exceeds 2.00%, the amount of ferrite increases, and the desired metal structure may not be obtained. Therefore, the Si content is preferably 2.00% or less. The Si content is more preferably 1.80% or less, 1.50% or less, 1.20% or less, 1.00% or less, or 0.80% or less. The Si content is preferably 0.05 to 1.80%, 0.10 to 1.50%, 0.20 to 1.20%, 0.30 to 1.00%, or 0.40 to 0.80%.
[0083] Mn: 0.10-3.00% Mn is an element that improves the hardenability of steel and contributes to improving strength. Therefore, the Mn content is preferably 0.10% or more. The Mn content is more preferably 0.20% or more, 0.50% or more, 1.00% or more, 1.30% or more, or 1.50% or more. On the other hand, if the Mn content exceeds 3.00%, Mn segregation may become significant. Therefore, the Mn content is preferably 3.00% or less. The Mn content is more preferably 2.80% or less, 2.50% or less, 2.30% or less, or 2.00% or less. The Mn content is preferably 0.20 to 2.80%, 0.50 to 2.50%, 1.00 to 2.30%, 1.30 to 2.00%, or 1.50 to 2.00%.
[0084] P:0.050% or less P is an impurity element and may cause a decrease in weldability. Therefore, the P content is preferably 0.050% or less. The P content is more preferably 0.030% or less, 0.020% or less, or 0.010% or less. There is no particular lower limit for the P content, but if it is reduced to less than 0.0001%, the dephosphorization cost increases significantly, which is economically undesirable. Therefore, the P content may be 0.0001% or more.
[0085] S: 0.0200% or less S is an impurity element and may cause a decrease in weldability. Therefore, the S content is preferably 0.0200% or less. The S content is more preferably 0.0180% or less, 0.0150% or less, 0.0100% or less, 0.0060% or less, or 0.0040% or less. There is no particular lower limit for the S content, but if it is reduced to less than 0.0001%, the cost of desulfurization increases significantly, which is economically undesirable. Therefore, the S content may be 0.0001% or more.
[0086] N: 0.0200% or less N is an impurity element and may cause a decrease in weldability. Therefore, the N content is preferably 0.0200% or less. The N content is more preferably 0.0180% or less, 0.0150% or less, 0.0100% or less, 0.0060% or less, or 0.0040% or less. There is no particular lower limit for the N content, but if it is reduced to less than 0.0001%, the cost of denitrification increases significantly, which is economically undesirable. Therefore, the N content may be 0.0001% or more.
[0087] O: 0.100% or less If a steel contains a large amount of O, it may cause a decrease in weldability. Therefore, the O content is preferably 0.100% or less. The O content is more preferably 0.0700% or less, 0.0500% or less, 0.0300% or less, 0.0100% or less, or 0.0050% or less. From the viewpoint of reducing refining costs, the O content may be 0.0001% or more, or 0.0005% or more.
[0088] Al: 0.001 to 0.100% Al is an element that has the effect of deoxidizing molten steel and improving the soundness of the steel. Therefore, the Al content is preferably 0.001% or more. The Al content is more preferably 0.005% or more, 0.010% or more, 0.015% or more, 0.020% or more, or 0.025% or more. On the other hand, if the Al content exceeds 0.100%, the effect is saturated, so the Al content is preferably 0.100% or less. The Al content is more preferably 0.080% or less, 0.060% or less, 0.040% or less, 0.020% or less, or 0.010% or less. The Al content is preferably 0.010 to 0.100%. The Al content is preferably 0.005 to 0.080%, 0.010 to 0.070%, 0.015 to 0.060%, 0.020 to 0.050%, or 0.025 to 0.040%.
[0089] Cr: 0.01~1.00% Cr is an element that improves the hardenability of steel. Therefore, the Cr content is preferably 0.01% or more. The Cr content is more preferably 0.03% or more, 0.05% or more, 0.10% or more, or 0.15% or more. On the other hand, if the Cr content exceeds 1.00%, the above effect is saturated, so the Cr content is preferably 1.00% or less. The Cr content is more preferably 0.80% or less, 0.60% or less, 0.50% or less, or 0.40% or less. The Cr content is preferably 0.03 to 0.80%, 0.05 to 0.60%, 0.10 to 0.50%, or 0.15 to 0.40%.
[0090] The basic chemical composition of the hot stamped steel according to the embodiment of the present invention is as described above. Furthermore, the hot stamped steel may contain at least one of the following optional elements in place of a portion of the remaining Fe, as necessary. The optional elements will be described in detail below.
[0091] Nb: 0 to 0.200% Nb is an element that forms carbonitrides in steel and improves the strength of hot stamped bodies by precipitation strengthening. The Nb content may be 0.0005% or more, but in order to reliably obtain this effect, the Nb content is preferably 0.001% or more or 0.002% or more. On the other hand, since the above effect saturates even if a large amount is contained, the Nb content is preferably 0.200% or less. The Nb content may be 0.180% or less, 0.150% or less, 0.100% or less, 0.050% or less, or 0.010% or less. The Nb content is preferably 0.0005 to 0.180%, 0.001 to 0.150%, 0.002 to 0.100%, 0.003 to 0.050%, or 0.004 to 0.010%.
[0092] Ti: 0 to 0.200% Ti is an element that forms carbonitrides in steel and improves the strength of hot stamped bodies by precipitation strengthening. The Ti content may be 0.001% or more, but in order to reliably obtain this effect, the Ti content is preferably 0.010% or more or 0.020% or more. On the other hand, even if a large amount is contained, the above effect is saturated, so the Ti content is preferably 0.200% or less. The Ti content may be 0.180% or less, 0.150% or less, 0.100% or less, 0.070% or less, or 0.040% or less. The Ti content is preferably 0.001 to 0.180%, 0.005 to 0.150%, 0.010 to 0.100%, 0.015 to 0.070%, or 0.020 to 0.040%.
[0093] Mo: 0 to 1.00% Mo is an element that improves the hardenability of steel. The Mo content may be 0.001% or more, but in order to reliably obtain this effect, the Mo content is preferably 0.003% or more or 0.005% or more. On the other hand, even if a large amount is contained, the above effect is saturated, so the Mo content is preferably 1.00% or less. The Mo content may be 0.80% or less, 0.60% or less, 0.50% or less, 0.30% or less, or 0.10% or less. The Mo content is preferably 0.001 to 0.80%, 0.002 to 0.60%, 0.003 to 0.50%, 0.004 to 0.30%, or 0.005 to 0.10%.
[0094] B: 0~0.0100% B is an element that improves the hardenability of steel. The B content may be 0.0001% or more, but in order to reliably obtain this effect, the B content is preferably 0.0005% or more or 0.0010% or more. On the other hand, since the above effect saturates even if a large amount is contained, the B content is preferably 0.0100% or less. The B content may be 0.0080% or less, 0.0060% or less, 0.0050% or less, 0.0030% or less, or 0.0020% or less. The B content is preferably 0.0001 to 0.0080%, 0.0003 to 0.0060%, 0.0005 to 0.0050%, 0.0007 to 0.0030%, or 0.0010 to 0.0020%.
[0095] Co: 0-4.00% Co is an element that improves the strength of the hot stamped body by solid solution strengthening. The Co content may be 0.001% or more, but in order to reliably obtain this effect, the Co content is preferably 0.01% or more or 0.05% or more. On the other hand, since the above effect saturates even if a large amount of Co is contained, the Co content is preferably 4.00% or less. The Co content may be 3.00% or less, 2.00% or less, 1.00% or less, 0.50% or less, or 0.10% or less. The Co content is preferably 0.001 to 3.00%, 0.005 to 2.00%, 0.01 to 1.00%, 0.03 to 0.50%, or 0.05 to 0.10%.
[0096] Ni: 0-2.00% Ni has the effect of increasing the strength of the hot stamped body by dissolving in austenite grains during heating in the hot stamp forming process. The Ni content may be 0.001% or more, but in order to reliably obtain this effect, the Ni content is preferably 0.01% or more. On the other hand, since the above effect saturates even if a large amount is contained, the Ni content is preferably 2.00% or less. The Ni content may be 1.80% or less, 1.60% or less, 1.40% or less, 1.20% or less, 1.00% or less, 0.50% or less, or 0.10% or less. The Ni content is preferably 0.001 to 1.80%, 0.005 to 1.60%, 0.01 to 1.40%, 0.02 to 1.20%, 0.03 to 1.00%, 0.04 to 0.50%, or 0.05 to 0.10%.
[0097] Cu: 0-1.00% Cu has the effect of increasing the strength of the hot stamped body by dissolving in austenite grains during heating in the hot stamp forming process. The Cu content may be 0.001% or more, but in order to reliably obtain this effect, the Cu content is preferably 0.01% or more or 0.05% or more. On the other hand, since the above effect saturates even if a large amount is contained, the Cu content is preferably 1.00% or less. The Cu content may be 0.80% or less, 0.60% or less, 0.50% or less, 0.30% or less, or 0.10% or less. The Cu content is preferably 0.001 to 0.80%, 0.005 to 0.60%, 0.01 to 0.50%, 0.03 to 0.30%, or 0.05 to 0.10%.
[0098] V: 0~1.00% V forms carbonitrides in steel and has the effect of improving the strength of hot stamped bodies by precipitation strengthening. The V content may be 0.001% or more, but in order to reliably obtain this effect, the V content is preferably 0.01% or more or 0.05% or more. On the other hand, since the above effect saturates even if a large amount is contained, the V content is preferably 1.00% or less. The V content may be 0.80% or less, 0.60% or less, 0.50% or less, 0.30% or less, or 0.10% or less. The V content is preferably 0.001 to 0.80%, 0.005 to 0.60%, 0.01 to 0.50%, 0.03 to 0.30%, or 0.05 to 0.10%.
[0099] W:0~1.00% W is an element that improves the hardenability of steel. The W content may be 0.001% or more, but in order to reliably obtain this effect, the W content is preferably 0.005% or more or 0.01% or more. On the other hand, since the above effect saturates even if a large amount is contained, the W content is preferably 1.00% or less. The W content may be 0.80% or less, 0.60% or less, 0.50% or less, 0.30% or less, or 0.10% or less. The W content is preferably 0.001 to 0.80%, 0.005 to 0.60%, 0.01 to 0.50%, 0.03 to 0.30%, or 0.05 to 0.10%.
[0100] Ca: 0 to 0.0100% Ca is an element capable of controlling the morphology of sulfides. The Ca content may be 0.0001% or more, but in order to reliably obtain this effect, the Ca content is preferably 0.0005% or more or 0.0010% or more. On the other hand, even if a large amount is contained, the above effect is saturated, so the Ca content is preferably 0.0100% or less. The Ca content may be 0.0080% or less, 0.0060% or less, 0.0040% or less, 0.0030% or less, or 0.0020% or less. The Ca content is preferably 0.0001 to 0.0080%, 0.0003 to 0.0060%, 0.0005 to 0.0040%, 0.0007 to 0.0030%, or 0.0010 to 0.0020%.
[0101] Magnesium: 0 to 0.0100% Mg is an element capable of controlling the morphology of sulfides. The Mg content may be 0.0001% or more, but in order to reliably obtain this effect, the Mg content is preferably 0.0005% or more or 0.0010% or more. On the other hand, since the above effect saturates even if a large amount is contained, the Mg content is preferably 0.0100% or less. The Mg content may be 0.0080% or less, 0.0060% or less, 0.0040% or less, 0.0030% or less, or 0.0020% or less. The Mg content is preferably 0.0001 to 0.0080%, 0.0003 to 0.0060%, 0.0005 to 0.0040%, 0.0007 to 0.0030%, or 0.0010 to 0.0020%.
[0102] REM: 0~0.0100% REM is an element capable of controlling the morphology of sulfides. The REM content may be 0.0001% or more, but in order to reliably obtain this effect, the REM content is preferably 0.0005% or more or 0.0010% or more. On the other hand, since the above effect saturates even if a large amount is contained, the REM content is preferably 0.0100% or less. The REM content may be 0.0080% or less, 0.0060% or less, 0.0040% or less, 0.0030% or less, or 0.0020% or less. The REM content is preferably 0.0001 to 0.0080%, 0.0003 to 0.0060%, 0.0005 to 0.0040%, 0.0007 to 0.0030%, or 0.0010 to 0.0020%.
[0103] In this embodiment, "REM" refers to Sc, Y, and lanthanoids, a total of 17 elements, and "REM content" refers to the content of one type of REM when there is one type, and the total content of two or more types when there are two or more types. REM is also generally supplied as misch metal, which is an alloy of multiple types of REM. For this reason, one or more individual elements may be added and contained, or they may be added in the form of misch metal, for example.
[0104] Sb: 0 to 0.100% Sb is an element that suppresses oxidation of the surface of the base steel sheet. To reliably obtain this effect, the Sb content is preferably 0.001% or more. On the other hand, even if a large amount of Sb is contained, the above effect is saturated, so the Sb content is preferably 0.100% or less. The Sb content may be 0.080% or less, 0.060% or less, 0.050% or less, 0.030% or less, or 0.010% or less. The Sb content is preferably 0.0001 to 0.080%, 0.0005 to 0.060%, 0.001 to 0.050%, 0.003 to 0.030%, or 0.005 to 0.010%.
[0105] Zr: 0 to 0.100% Zr is an element that suppresses oxidation of the surface of the base steel sheet. To reliably obtain this effect, the Zr content is preferably 0.001% or more. On the other hand, even if a large amount is contained, the above effect is saturated, so the Zr content is preferably 0.100% or less. The Zr content may be 0.080% or less, 0.060% or less, 0.050% or less, 0.030% or less, or 0.010% or less. The Zr content is preferably 0.0001 to 0.080%, 0.0005 to 0.060%, 0.001 to 0.050%, 0.003 to 0.030%, or 0.005 to 0.010%.
[0106] Sn: 0 to 1.00% Sn is an element that suppresses oxidation of the surface of the base steel sheet. To reliably obtain this effect, the Sn content is preferably 0.001% or more. On the other hand, even if a large amount of Sn is contained, the above effect is saturated, so the Sn content is preferably 1.00% or less. The Sn content may be 0.800% or less, 0.500% or less, 0.200% or less, 0.100% or less, 0.050% or less, or 0.010% or less. The Sn content is preferably 0.0001 to 0.800%, 0.0005 to 0.500%, 0.001 to 0.200%, 0.002 to 0.100%, 0.003 to 0.050%, or 0.005 to 0.010%.
[0107] As: 0~0.100% As has the effect of increasing the strength of the hot stamped body. To reliably obtain this effect, the As content is preferably 0.001% or more. On the other hand, even if a large amount of As is contained, the above effect saturates, so the As content is preferably 0.100% or less. The As content may be 0.080% or less, 0.050% or less, 0.020% or less, 0.010% or less, or 0.005% or less. The As content is preferably 0.001 to 0.080%, 0.002 to 0.050%, 0.003 to 0.020%, 0.004 to 0.010%, or 0.005 to 0.005%.
[0108] In the chemical composition of the hot stamped steel according to the present embodiment, the balance other than the above elements is Fe and impurities. The impurities are components that are mixed in due to various factors in the manufacturing process, including raw materials such as ores and scraps, during industrial production of the hot stamped steel.
[0109] As described above, when the balance between hydrogen embrittlement resistance and notch tensile strength of the hot stamped steel is important, it is preferable for the hot stamped steel to have a strength of 1.5 GPa. To obtain this strength, the chemical composition of the hot stamped steel, in mass%, is C: 0.18-0.26%, Si: 0.05-0.30%, Mn: 0.80-1.60%, P: 0.050% or less, S: 0.0200% or less, N: 0.0200% or less, O: 0.100% or less, Al: 0.005-0.080%, Cr: 0.10-0.50%, Nb: 0-0.020%, Ti: 0.010-0.050%, Mo: 0.010-0.050%, and the like. It is preferable that the composition is selected from the group consisting of: B: 0.0010-0.0050%, Co: 0-4.00%, Ni: 0-2.00%, Cu: 0-1.00%, V: 0-1.00%, W: 0-1.00%, Ca: 0-0.0100%, Mg: 0-0.0100%, REM: 0-0.0100%, Sb: 0-0.100%, Zr: 0-0.100%, Sn: 0-1.00%, As: 0-0.100%, and the balance: Fe and impurities.
[0110] The chemical composition of the above-mentioned hot stamped body may be measured by a general analytical method. For example, it may be measured using ICP-AES (Inductively Coupled Plasma-Atomic Emission Spectrometry). C and S may be measured using a combustion-infrared absorption method, N may be measured using an inert gas fusion-thermal conductivity method, and O may be measured using an inert gas fusion-non-dispersive infrared absorption method. When the hot stamped body has a plating layer on its surface, the plating layer may be removed by mechanical grinding before the chemical composition is analyzed.
[0111] 4. Manufacturing method An example of a method for producing a hot stamped steel according to the present embodiment will be described.
[0112] First, a steel plate (blank) is manufactured as the raw material for the hot stamped body. Molten steel having the above-mentioned chemical composition is manufactured, and a slab is manufactured using this molten steel. As the slab to be subjected to hot rolling, a continuous cast slab or one manufactured by a thin slab caster or the like can be used. The above-mentioned manufacturing method of steel plate is suitable for processes such as continuous casting-direct rolling (CC-DR), in which hot rolling is performed immediately after casting.
[0113] The slab heating temperature is preferably 1100° C. or higher. A slab heating temperature in the temperature range below 1100° C. leads to a decrease in the finish rolling temperature, and the strength during finish rolling tends to be high. As a result, rolling may become difficult or the shape of the steel sheet after rolling may become defective, so the slab heating temperature is preferably 1100° C. or higher.
[0114] The finish rolling completion temperature is preferably 800°C or higher. If the finish rolling completion temperature is lower than 800°C, the rolling load increases, which may make rolling difficult or cause a defective shape of the steel sheet after rolling, so the lower limit of the finish rolling completion temperature is preferably 800°C. There is no need to particularly determine the upper limit of the finish rolling completion temperature, but if the finish rolling completion temperature is made too high, the slab heating temperature must be made too high to ensure that temperature, so the upper limit of the finish rolling completion temperature is preferably 1100°C. After the completion of finish rolling, the average cooling rate to the coiling temperature described below is preferably 10 to 100°C / s.
[0115] The coiling temperature is preferably 700°C or less. If the coiling temperature exceeds 700°C, the thickness of the oxide formed on the steel sheet surface may be excessively increased, which may reduce the pickling property. If cold rolling is performed after this, the lower limit of the coiling temperature is preferably 400°C. If the coiling temperature is less than 400°C, the strength of the hot-rolled steel sheet increases extremely, which is likely to induce sheet breakage and shape defects during cold rolling, so the lower limit of the coiling temperature is preferably 400°C. However, if the coiled hot-rolled steel sheet is heated in a box-type annealing furnace or continuous annealing equipment to soften it, it may be coiled at a low temperature of less than 400°C. In addition, the rough-rolled sheets may be joined together during hot rolling and finish rolling may be performed continuously. The rough-rolled sheet may also be coiled once.
[0116] The hot-rolled steel sheet may be subjected to pickling treatment, and the hot-rolled steel sheet after the pickling treatment may be cold-rolled to obtain a cold-rolled steel sheet. When cold-rolling is performed, the rolling reduction may be, for example, 30 to 80%. The pickling treatment may be performed by immersing the steel sheet in an aqueous solution containing an inhibitor and having an acid concentration of 3 to 20 mass% at a temperature of 80°C or more and less than 100°C for 30 seconds or more. Furthermore, the hot-rolled steel sheet or cold-rolled steel sheet may be annealed to obtain a hot-rolled annealed sheet or cold-rolled annealed sheet. The annealing is performed by passing the steel sheet through a continuous annealing line, and the annealing temperature may be, for example, in the range of 550 to 750°C.
[0117] The obtained various steel sheets may be subjected to a plating treatment before hot stamp forming. The plating to be applied is not particularly limited, but examples thereof include hot-dip galvanizing, alloyed hot-dip galvanizing, electrogalvanizing, Zn-Ni plating (electroalloy galvanizing), Sn plating, Al-Si plating, alloyed electrogalvanizing, hot-dip zinc-aluminum alloy plating, hot-dip zinc-aluminum-magnesium alloy plating, hot-dip zinc-aluminum-magnesium alloy-Si plating, and zinc vapor deposition Al plating. The plating treatment can be performed by passing the sheet through a continuous line.
[0118] Next, the blank is subjected to hot stamp forming. In this process, the blank is heated, and then press formed and quenched. In quenching, the blank is held in a die and cooled to a temperature below the Mf point by removing heat from the die. When manufacturing a hot stamped body having a burred portion, burring may be performed simultaneously or continuously with press forming, and then quenching may be performed immediately.
[0119] In order to form the above-mentioned first region and second region in the hot stamped steel, it is important to control the heating conditions before hot stamping.
[0120] For areas where high strain is not expected to be added (hereinafter also referred to as "low strain areas"), the material is heated to a temperature between Ac3 point + 65°C and Ac3 point + 65°C at an average heating rate of 2 to 200°C / s, and then held in that temperature range for 10 to 120 seconds. On the other hand, for areas where high strain is expected to be added (hereinafter also referred to as "high strain areas"), the material is heated to a temperature between Ac3 point + 40°C and Ac3 point + 110°C, and 40°C higher than the heating temperature for the low strain areas, at an average heating rate of 2 to 200°C / s and at least the average heating rate for the low strain areas, and then held in that temperature range for 10 to 120 seconds.
[0121] Methods for creating a difference in the heating rate and heating temperature between the two parts include: (1) applying a surface treatment such as a black coating only to the high strain part to change the surface emissivity; (2) creating a temperature distribution within the furnace when heating in a furnace; (3) inserting a shield between the low strain part and the heat source within the furnace when heating in a furnace; and (4) making the plate width of the high strain part smaller than that of the low strain part when heating by electrical current to change the electrical resistance.
[0122] After the blank is removed from the furnace, forming is started. At this time, the temperature at the start of forming is 700°C or higher for both parts. Then, quenching is performed by cooling to a temperature below the Mf point without demolding. At this time, the average cooling rate from the forming start temperature to the Ms point is 50°C / s or higher and lower than 150°C / s, and the average cooling rate from the Ms point to the Mf point is 10°C / s or higher. After demolding in the temperature range below the Mf point, it is sufficient to leave it to cool to room temperature at an average cooling rate of, for example, 5°C / s or lower.
[0123] By performing hot stamp forming under the above conditions, it is possible to suppress the coarsening of the metal structure in the low strain portion, suppress the decrease in strength, hydrogen embrittlement resistance, and notch tensile strength, while suppressing the formation of ferrite in the high strain portion, thereby forming a first region from the low strain portion and a second region from the high strain portion.
[0124] If the heating temperature in the low strain region is below the Ac3 point, structures other than austenite, such as ferrite, pearlite, bainite, and cementite, may remain after heating, and the area ratio of martensite may become less than 95% during the subsequent cooling process. On the other hand, if the heating temperature in the low strain region exceeds the Ac3 point + 65°C or the heating time exceeds 120 seconds, the crystal grains may become coarse, and the hydrogen embrittlement resistance and notch tensile strength may decrease.
[0125] Furthermore, if the heating temperature in the highly strained region is below Ac3 point + 40°C, the grains will not be coarsened sufficiently, sufficient hardenability will not be obtained, ferrite will be formed, and the area ratio of martensite after cooling may be less than 95%. On the other hand, if the heating temperature in the highly strained region is above Ac3 point + 110°C or the heating time exceeds 120 seconds, the grains will be excessively coarsened, and hydrogen embrittlement resistance and notch tensile strength may be reduced.
[0126] In addition, when the strength of the hot stamped product is 1.5 GPa class, G1 is in the range of 8.0 to 14.0 μm, and G2 is in the range of 17.0 to 25.0 μm, it is preferable that the heating temperature in the low strain region is Ac3 point + 10° C. or more and Ac3 point + 60° C. or less, and the heating temperature in the high strain region is Ac3 point + 70° C. or more and Ac3 point + 110° C. or less. It is more preferable that the heating temperature in the low strain region is Ac3 point + 15° C. or more and Ac3 point + 50° C. or less, and the heating temperature in the high strain region is Ac3 point + 75° C. or more and Ac3 point + 100° C. or less.
[0127] Furthermore, when the difference between the heating temperature in the high strain region and the heating temperature in the low strain region is less than 40°C, the difference between the average grain size G1 in the first region and the average grain size G2 in the second region becomes small, and the above formula (i) cannot be satisfied. As a result, it becomes impossible to simultaneously achieve finer structure in the low strain region and suppression of ferrite formation in the high strain region.
[0128] Furthermore, if the forming start temperature is less than 700°C, a large amount of ferrite may be formed during air cooling from after heating to the start of forming, or during the subsequent cooling process, and the area ratio of martensite may become less than 95%.
[0129] If the average cooling rate from the forming start temperature to the Ms point is less than 50°C / s, a large amount of ferrite may be generated during the cooling process, and the area ratio of martensite may be less than 95%. If the average cooling rate from the Ms point to the Mf point is less than 10°C / s, the strength may decrease due to self-tempering. If the mold is released at a temperature above the Mf point, martensitic transformation may occur even after release, and the dimensional accuracy of the molded body may decrease.
[0130] In the present invention, the Ac3 point, the Ms point and the Mf point are determined based on the following formulas (I) to (III), respectively. Ac3(℃)=850+10×(C+N)×Mn+350×Nb+250×Ti+40×B+10×Cr+100×Mo...(I) Ms(℃)=550-361×C-39×Mn-35×V-20×Cr-17×Ni-10×Cu-5×(Mo+W)+15×Co+30×Al...(II) Mf(℃)=410.5-407.3×C-7.3×Si-37.8×Mn-20.5×Cu-19.5×Ni-19.8×Cr-4.5×Mo...(III) In the above formula, the element symbols represent the content (mass %) of each element.
[0131] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to these examples. EXAMPLES
[0132] Molten steel (steel types a to r) having the chemical compositions shown in Table 1 were cast by continuous casting to produce slabs. These slabs were heated to a temperature of 1100°C or higher, and then rough rolling, finish rolling, cooling, and coiling were performed under the conditions shown in Table 2 to produce hot-rolled steel sheets. Thereafter, the hot-rolled steel sheets of steel types f and k were further cold-rolled to produce cold-rolled steel sheets.
[0133] [Table 1]
[0134] [Table 2]
[0135] The obtained hot-rolled or cold-rolled steel sheet was subjected to hot stamp forming, which involves a series of steps including press forming, burring, and quenching, under the conditions shown in Tables 3 and 4, to produce a hot-stamped product having a shape shown in FIG. 1 and a plate-shaped part and a burring part. The thickness of the plate-shaped part was 2.6 mm, the thickness of the tip of the burring part (end thickness) was the thickness shown in Tables 5 and 6, and the diameter of the burring part was 50 mm. At this time, a black coating was applied to the part scheduled for burring (the part that will become the burring part after hot stamp forming) and the emissivity of the surface was changed to provide a difference in heating rate and heating temperature between the part scheduled for burring (the part that will become the plate-shaped part after hot stamp forming) and the part scheduled for burring (the part that will become the plate-shaped part after hot stamp forming).
[0136] [Table 3]
[0137] [Table 4]
[0138] In the table, "heating rate" and "heating temperature" refer to the average heating rate and heating temperature during heating before hot stamp forming. "Difference from Ac3 point" refers to the value obtained by subtracting Ac3 point from the above heating temperature. "Holding time" refers to the time held at the above heating temperature. "St-Ms cooling rate" refers to the average cooling rate from the forming start temperature St to the Ms point, and "Ms-Mf cooling rate" refers to the average cooling rate from the Ms point to the Mf point. "Heating temperature difference" refers to the value obtained by subtracting the heating temperature at a portion where burring processing is planned from the heating temperature at a portion where burring processing is not planned.
[0139] Next, the cross sections shown in Figures 1, 2 and 8 were used as the measurement areas of the plate-shaped part and the burred part, respectively, and the metal structure was observed and the Vickers hardness was measured by the following methods. The measurement results are shown in Tables 5 and 6.
[0140] [Table 5]
[0141] [Table 6]
[0142] First, the measurement area was etched with nital, and after etching, it was photographed at 1000 times magnification using FE-SEM. The FE-SEM used was equipped with a secondary electron detector. Then, image analysis was performed on the obtained structural photograph to measure the area ratio of structures judged to be ferrite or pearlite, and the rest were judged to be martensite, bainite, or retained austenite. The total area ratio judged to be martensite, bainite, or retained austenite is shown as "M+B+γ area ratio (%)" in Tables 5 and 6. If the area ratio was less than 95%, it was judged that the martensite area ratio ("M area ratio" in Tables 5 and 6) was less than 95% ("<95%").
[0143] On the other hand, when the area ratio was 95% or more, a mesh was drawn at 70 μm intervals in an area of 300 μm length and 2000 μm width, and Vickers hardness was measured at all intersections of the mesh. The test force for the Vickers hardness measurement was 0.98 N (0.1 kgf). After that, the specimen was photographed again at 1000 times magnification using FE-SEM. Then, by comparing the structural photographs taken before and after the Vickers hardness measurement, it was determined whether the area of the depressions remaining on the surface contained structures other than martensite, bainite, and retained austenite, i.e., ferrite or pearlite.
[0144] Among the obtained Vickers hardness measurements, the average of the measurements that were identified as indicating that the indentations contained only martensite, bainite, or retained austenite was calculated, and if the following formula was satisfied, it was determined that the area ratio of martensite in the metal structure was 95% or more ("≧95%). On the other hand, if the following formula was not satisfied, it was considered that the area ratio of bainite was relatively high or that the martensite had been excessively tempered, so it was determined that the area ratio of martensite was less than 95% ("<95%), and no further observation of the metal structure was performed. HV MBγ ≧957.1×[C]+221.0 In the above formula, the meanings of each symbol are as follows: HV MBγ : Average Vickers hardness measurement value (HV0.1) that identifies an indentation as containing only martensite, bainite or retained austenite [C]: C content of hot stamped compact (mass%)
[0145] In addition, the average values of the measured Vickers hardness at all intersections of the mesh with 70 μm intervals in the observation areas of the plate-like part and the burred part are also shown in Tables 5 and 6 as HV1 and HV2, respectively.
[0146] Next, the observation area was mirror-polished and electrolytically polished under the above-mentioned conditions, and then measurements were performed using EBSD to identify prior austenite grains using the reconstruction method described above. The grain size and aspect ratio of each identified prior austenite grain were determined, and the average grain size and average aspect ratio were calculated by averaging the measured values for all prior austenite grains in the observation area.
[0147] Next, the tensile strength, hydrogen embrittlement resistance, and notched tensile strength of each hot stamped steel were evaluated by the following methods.
[0148] <Tensile strength> Sub-size plate test pieces (width 10 mm, total length 100 mm, parallel part width 6.25 mm, parallel part length 32 mm, gauge length 25 mm, thickness: original thickness of plate part) as specified in ASTM A370-22, shown in Fig. 9, were prepared from the plate part of each hot stamped body. The half-size plate test pieces were then used to perform a tensile test to measure the tensile strength TS (MPa). In this case, the tensile speed was 3 mm / min at the crosshead displacement speed, and the other conditions were in accordance with JIS Z 2241:2022.
[0149] <Hydrogen embrittlement resistance and notched tensile strength> Test pieces were cut out from each of the plate-shaped part and the burring part of the hot stamped body, and two tensile test pieces having the shape shown in FIG. 10 were prepared. FIG. 11 is a diagram for explaining the procedure for cutting out test pieces from the burring part and preparing tensile test pieces. Due to the size of the burring part, it is not possible to obtain a tensile test piece having the shape shown in FIG. 10 from the burring part. Therefore, as shown in FIGS. 11(a) and 11(b), a test piece having a length of 8.0 mm, a thickness of 1.0 mm, and a height of 2.0 mm was first cut out from the tip of the burring part 12. Then, as shown in FIG. 11(c), U-notches were formed on both sides of the center of the test piece, and then, as shown in FIG. 11(d), dummy materials shown by hatches were joined by welding to both sides to obtain a tensile test piece having the same shape as that shown in FIG. 10.
[0150] One of the tensile test pieces was placed in a 3% NaCl aqueous solution as the cathode, and a current density of 1.0 mA / cm 2 While generating hydrogen on the surface of the tensile test piece under the above conditions, a tensile test was performed at a tensile speed of 0.006 mm / min, and the fracture stress (maximum stress) in a hydrogen environment was measured. Note that Pt was used as the anode. The measured value was taken as the tensile strength in a hydrogen environment TSH (MPa), which was used as an index of hydrogen embrittlement resistance.
[0151] The other tensile test piece was subjected to a tensile test in accordance with JIS Z 2241:2022 at 0.006 mm / min in air to measure the breaking stress (maximum stress). The measured value was taken as the notched tensile strength TSN (MPa).
[0152] In this example, when the sum of the measured tensile strength in a hydrogen environment and the notched tensile strength, TSH+TSN (MPa), was 2400 MPa or more, it was determined that the steel had excellent hydrogen embrittlement resistance and high notched tensile strength.
[0153] The results are shown in Table 7.
[0154] [Table 7]
[0155] As shown in Tables 5 to 7, test numbers 1 to 8, 20 to 24, 26 to 28, and 30 to 40, which satisfy the provisions of the present invention, had high strength and suppressed a decrease in strength even in the burred portion, and it was possible to achieve both excellent hydrogen embrittlement resistance and high notch tensile strength.
[0156] In contrast, in test numbers 9 to 19, 25, and 29, in which the hot stamping conditions were inappropriate, the martensite area ratio was less than 95% in at least one of the plate-shaped portion and the burred portion, or the average crystal grain size exceeded the specified value. As a result, softening occurred due to the formation of ferrite, or the effects of improving hydrogen embrittlement resistance and notch tensile strength could not be obtained.
[0157] Specifically, in test number 9, the heating temperature was high in the area where burring was not planned, and the difference in heating temperature between the area where burring was planned was small, so the average crystal grain size G1 in the plate-shaped part was excessive, and the difference (G2-G1) with the average crystal grain size G2 in the burring part did not satisfy the regulation. As a result, TSH+TSN in the plate-shaped part decreased.
[0158] In test number 10, the heating temperature at the part scheduled for burring was high, so the average crystal grain size G2 at the burring part was excessive. As a result, TSH+TSN decreased at the burring part.
[0159] In test number 11, the heating temperature was high in the area where burring was not planned, and low in the area where burring was planned, so the average grain size G1 in the plate-shaped part was excessive, and the area ratio of martensite in the burred part was not 95% or more. As a result, TSH+TSN decreased in both the plate-shaped part and the burred part.
[0160] In test number 12, the heating temperature was high and the heating time was long in the area where burring was not planned and the area where burring was planned, and the difference in heating temperature between the two areas was small. Therefore, the average crystal grain size G1 in the plate-shaped part and the average crystal grain size G2 in the burring part were both excessive, and the difference between the two (G2-G1) did not satisfy the regulation. As a result, TSH+TSN decreased in both the plate-shaped part and the burring part.
[0161] In test number 13, the area ratio of martensite did not reach 95% or more in the plate part and the burred part because the forming start temperature was low in the area not scheduled for burring and the area scheduled for burring. As a result, TSH+TSN decreased in both the plate part and the burred part.
[0162] In test number 14, the average cooling rate from the forming start temperature to the Ms point was low in the areas not scheduled for burring and in the areas scheduled for burring, so the area ratio of martensite did not reach 95% or more in the plate and burred parts. As a result, TSH+TSN decreased in both the plate and burred parts.
[0163] In test number 15, the average cooling rate from the Ms point to the Mf point was low in the area where burring was not planned and in the area where burring was planned, so the area ratio of martensite did not reach 95% or more in the plate-shaped part and the burred part. As a result, the necessary strength was not obtained in the plate-shaped part.
[0164] In test number 16, the heating temperature was low in the area where burring was planned, and the difference in heating temperature between the area where burring was not planned was small, so the area ratio of martensite in the burred area did not reach 95% or more. As a result, TSH+TSN decreased in the burred area.
[0165] In test number 17, the heating temperature in the area where burring was not planned was low, so the area ratio of martensite in the plate-shaped part did not reach 95% or more. As a result, the necessary strength was not obtained in the plate-shaped part, and TSH+TSN also decreased.
[0166] In test number 18, the heating temperature was high in the area where burring was not planned, and the difference in heating temperature between the area where burring was planned was small, so the average crystal grain size G1 in the plate-shaped part was excessive, and the difference (G2-G1) with the average crystal grain size G2 in the burring part did not satisfy the regulation. As a result, TSH+TSN decreased in the plate-shaped part.
[0167] In test number 19, the heating temperature was high and the heating time was long in the area where burring was not planned and the area where burring was planned, and the difference in heating temperature between the two areas was small. Therefore, the average crystal grain size G1 in the plate-like part and the average crystal grain size G2 in the burring part were both significantly excessive. As a result, TSH+TSN decreased in both the plate-like part and the burring part.
[0168] In test number 25, the heating temperature was high in the area where burring was not planned, and the difference in heating temperature between the area where burring was planned was small, so the average crystal grain size G1 in the plate-shaped part was excessive, and the difference with the average crystal grain size G2 in the burring part (G2-G1) did not satisfy the regulation. As a result, TSH+TSN in the plate-shaped part decreased.
[0169] In test number 29, the heating temperature was high in the area where burring was not planned and in the area where burring was planned, and the difference in heating temperature between the two areas was small. Therefore, the average crystal grain size G1 in the plate-shaped area and the average crystal grain size G2 in the burring area were both excessive, and the difference between the two (G2-G1) did not satisfy the regulation. As a result, TSH+TSN decreased in both the plate-shaped area and the burring area. [Industrial Applicability]
[0170] According to the present invention, even when high strain is locally introduced in the hot stamping process, it is possible to obtain a hot stamped steel in which the decrease in strength after hot stamping in the high strain region is suppressed.
Claims
1. A first region having a metal structure in which an area ratio of martensite is 95% or more and an average aspect ratio of prior austenite grains is 1.10 or less; A second region having a metal structure in which the area ratio of martensite is 95% or more and the average aspect ratio of prior austenite grains is 2.00 or more, When the average grain size of the prior austenite grains in the first region is G1 (μm) and the average grain size of the prior austenite grains in the second region is G2 (μm), G1 is 15.0 μm or less and G2 is 25.0 μm or less, and the following formula (i) is satisfied: The tensile strength measured by a tensile test using a test piece taken from the first region is 1250 to 2540 MPa. Hot stamped compact. G2-G1≧3.0...(i)
2. The average grain size G1 of the prior austenite grains in the first region is 5.0 to 15.0 μm, and the average grain size G2 of the prior austenite grains in the second region is 10.0 to 25.0 μm. The hot stamped product according to claim 1 .
3. The chemical composition, in mass%, is C: 0.10-0.60%, Si: 0.01-2.00%, Mn: 0.10-3.00%, P: 0.050% or less, S: 0.0200% or less, N: 0.0200% or less, O: 0.100% or less, Al: 0.001-0.100%, Cr: 0.01-1.00%, Nb: 0 to 0.200%, Ti: 0-0.200%, Mo: 0-1.00%, B: 0 to 0.0100%, Co: 0-4.00%, Ni: 0-2.00%, Cu: 0 to 1.00%, V: 0-1.00%, W: 0-1.00%, Ca: 0-0.0100%, Mg: 0 to 0.0100%, REM: 0-0.0100%, Sb: 0 to 0.100%, Zr: 0 to 0.100%, Sn: 0-1.00%, As: 0 to 0.100%, The balance is Fe and impurities. The hot stamped product according to claim 1 or 2.
Citation Information
Patent Citations
Manufacturing method of hot press product
JP2019058916A
Hot-stamp-molded article, process for production of steel sheet for hot stamping, and process for production of hot-stamp-molded article
WO2011158818A1
Hot-press member and method for producing same, and cold-rolled steel sheet for hot pressing
WO2019003445A1
Press molded steel article
WO2019198781A1
Duplex stainless steel pipe and method for manufacturing same
WO2022196196A1